The impact of China pilot carbon market policy on electricity carbon emissions - Zelong Zhang; Yanli Xiao; Kun Zhang; Mengyuan Tang; Ting Ma (Scientific Reports)
Abstract The electric power industry is the pillar of the national economy but also the largest carbon emission sector in China, facing great pressure to reduce emissions. Existing research often lacks the analysis of the carbon market on electricity carbon emission reduction. Based on the panel data of 30 provinces (cities) in China from 2003 to 2020, we combine the multi-period difference-in-differences model with the spatial Durbin model to explore the effectiveness of the pilot carbon market policy on electricity carbon emission reduction, the mechanism of its role, and its spatial spillover effect. The results show that: (1) The carbon market policy in the electric power industry can effectively play the carbon emission reduction effect, but its spatial spillover effect exists in the carbon emission transfer phenomenon to weaken the overall emission reduction effect. (2) The pilot carbon market policy mainly promotes carbon emission reduction in the power industry by strengthening government intervention and reducing power energy consumption, and the role of R&D innovation intensity has not yet been substantially realized. (3) The impact of pilot carbon market policies on electricity carbon emission reduction varies according to the degree of emphasis on environmental governance and regional features. The conclusion provides feasible suggestions for policymakers to strengthen the mechanism design of the carbon market in the power industry, which is of great significance for realizing the goal of “double carbon.”